The influence of organizational culture and transformational leadership on employee performance PT. Epson in the digital era - Manalu, Nelly Chandrawati (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the influence of organizational culture and transformational leadership on employee performance in the digital era. Methodology: This study uses a quantitative method with a survey approach; data were collected through questionnaires from 150 respondents who are employees at PT. Epson. Data analysis was carried out using multiple linear regression to test the relationship between variables. Results: This study proves that organizational culture and transformational leadership have a positive and significant influence on employee performance, including in the context of the digital era. This is indicated by a calculated t-value greater than the t-table (1.96) and a P-value <0.050 for all hypotheses. Thus, all hypotheses proposed in this study are accepted. Conclusions: The conclusion of this study confirms that the implementation of a strong organizational culture and transformational leadership are key strategies to increase productivity in the digital era. This research was conducted in the context of increasingly massive digitalization, thus providing a new perspective on how organizational culture and leadership styles need to adapt to face technological changes and the need for more flexible and data-driven work. Limitations: This study uses a quantitative approach through distributing questionnaires, so it cannot capture in depth the perceptions, emotions and dynamics of social interactions within the organization. Contribution: Providing input to company leaders in developing a work culture that is adaptive to digital change. The company needs to strengthen an organizational culture that is adaptive, innovative, and open to technological change. Furthermore, implementing transformational policies is crucial to boost employee motivation, loyalty, and productivity.